A.C. Conductivity of Ag Incorporated Se-Te-Bi Glassy Alloy - Anup Kumar; Pawan Heera; Raman Sharma (Журнал нано- та електронної фізики)
Effect of Ag addition on the a.c. conductivity as a function of frequency in Se80.5Bi1.5Te18 – yAgy (y  1.0, 1.5 and 2.0 at. %) glassy alloy has been investigated in the temperature range 300-355 K. The electrical conductivity is measured as a function of frequency () of an alternating electric field in the frequency range 1 -500 kHz, using Wayne Kerr 6500 B Impedance Analyzer. A.C. conductivity (ω) is found to increases with an increase in frequency for the entire range of temperature in all compositions. The frequency exponent s is found to decrease with an increase in temperature which indicates that the correlated barrier hopping is the possible conduction mechanism in the investigated samples.